THE UTILIZATION OF LOCAL FOLKLORE AS TEACHING MATERIAL: STUDENTS' VIEWPOINT AND CHARACTER EDUCATION - Barli, Jenny; Surtikanti, Monika Widyastuti; Agung, Antonius Setyawan Sugeng Nur (Journal of English Educational Study (JEES), 2024)
This research aims to explore students' perceptions of the utilization of local folklore as the English teaching material and investigate the character education in it. The local folklore used in this study is Ne’ Balungkur, the Dayak Kanayat’n Myth. The character education was analyzed based on character education available in the Curriculum Center of the Research and Development Agency of the Ministry of National Education. The researchers employed a qualitative descriptive method to describe students' views on the local folklore of Ne' Balungkur & analyze the character education. The findings revealed that the students are interested and motivated when they learned narrative text using Ne’ Balungkur folklore. They also found that the folklore allowed them to gain new information and English vocabulary. Ne' Balungkur folklore incorporate educational characters included in the types of educational characters such as religious, discipline, hardworking, creative, independent, curiosity, friendly, social care, and responsibility. Future study might explore more about local folklore as teaching media with different perspective. Keywords: local folklore, teaching material, students’ viewpoint, character education